Development of user interface of tele-operated cranes - Chi, Hung-Lin; Chen, Y.; Kang, S.; Hsieh, S. (Elsevier Ltd, 2012)
This research focuses on one of the major challenges in a tele-operated crane system, namely the userinterface (UI). This UI should provide rich information retrieved from the field and display it properlyin order to enhance the operation and decision-making processes involved in crane activities. In thisresearch, we have designed two UIs specifically for a tele-operated crane system. The first UI is a fourview system (quad-view) with a top view, left-side view, right-side view, and global view. The secondUI has four views but uses additional guidance from Augmented Reality (AR) technologies. To test theUIs, we used a robot arm (KUKA KR16) to simulate a tele-operated crane in a testing environment. Wealso compared the UIs we designed against a conventional operation interface (i.e. operator’s view withoral guidance from the ground). We conducted a user test with two groups of participants: 5 crane operatorsand 30 students. Students constitute a novice group, and their results are interpreted from a statisticalperspective. Using the student group, the interface’s learning curve can be evaluated. Operatorsconstitute an expert group, which provides evidences for evaluating if the developed UIs are realisticand fit the needs of the field. We found that use of the UIs we designed resulted in a shorter erection time(336 and 343 s) than if the participants used the conventional operation interface (380 s). A self-evaluatedindex showing the difficulty of the tasks, the NASA task loading index (TLX), was calculated for eachof the UIs. The UIs resulted in a higher TLX (52.0 and 53.2) than the conventional operation interface(32.2). In summary, the two UIs developed in this research are able to assist operators in operatingremote cranes more efficiently and with less mental load than by using the conventional operationinterface.